A new EEG recording and electrical stimulation medical device with independent feedback control function - Du, Yuxiao; Sun, Bo; Zhang, Chunling; Chen, Feng (Chinese Control Conference, 2019)
In this paper, a new type of EEG recording and electrical stimulation medical device with self-feedback function which using a microelectrode array is developed for the diagnosis and treatment of cranial nerve diseases. The main research of this paper is as follows: (1) Weak brain signal acquisition technology. It uses a noise suppression method without power frequency notch to obtain the true synchronous pulse width EEG waveform in this device. (2) Microcurrent stimulation technology. This device is designed with triple hardware protection and precision constant current source to meet clinical safety and high precision requirements. (3) An expert system for autonomous feedback control of stimulating currents. In this system, it uses a filter with infinite impulse response to preprocess the signal. And it uses wavelet transform combined with mathematical statistics method to extract EEG time-frequency information, integrated fuzzy c-means clustering search algorithm and expert system to control stimulation current. There are the functions of evoked potentials by using EEG nerve electrical stimulation and of using micro-current stimulation to feedback therapy in this device. It can be used for precise location of epilepsy lesions and clinical diagnosis of brain diseases such as Parkinson's disease. It can also be used for neurological rehabilitation treatments such as depression, insomnia, and brain function disorders. This equipment has important scientific significance and application value for the research of cranial nerve clinical medicine, brain nerve function loop foundation and brain-computer interface.